(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Diarrhea is still a major health problem in developing countries, especially in Indonesia. One of the ways to prevent diarrhea is by implementing a Clean and Healthy Lifestyle (PHBS) for the family. However, PHBS in Indonesia is still below the national target, as is the 23 Ilir Health Center. This study aims to determine the analysis of clean and healthy living behavior with the incidence of diarrhea at Puskesmas 23 Ilir Palembang in 2022. It was carried out in May - June 2022. This study was quantitative with a cross sectional design, the population of this study were mothers who had toddlers at Puskesmas 23 Ilir. Palembang returned 91 samples. Data collection and retrieval using a questionnaire. The results of statistical analysis using Chi-Square statistical tests and logistic regression where the results showed there was a significant relationship (p value <0.05) for the variable exclusive breastfeeding (0.01) with the incidence of diarrhea in children under five. There is no relationship between the variables weighing toddlers every month (0.22), using clean water (0.069), washing hands with soap and clean water (0.072), and using healthy latrines (0.583). From the results of multivariate statistical tests, it was found that the dominant factor for clean and healthy living behavior with the incidence of diarrhea in toddlers was exclusive breastfeeding (p = 0.000; OR = 5,135). It is recommended for health workers to provide counseling about the importance of exclusive breastfeeding related to the incidence of diarrhea in toddlers.